2017
DOI: 10.1111/tmi.12922
|View full text |Cite
|
Sign up to set email alerts
|

Impact of China's essential medicines scheme and zero‐mark‐up policy on antibiotic prescriptions in county hospitals: a mixed methods study

Abstract: The national essential medicines scheme and zero-mark-up policy, when implemented with an antimicrobial stewardship programme, may be associated with reductions in outpatient antibiotic prescribing and intravenous infusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 21 publications
0
54
1
Order By: Relevance
“…Despite the implementation of the National Essential Medicines Policy and Zero-Mark-Up Policy in 2009 and the Administrative Regulation for Clinical Antibiotic Use in 2012 [16], their effects on reducing inappropriate antibiotic prescribing have been limited to large hospitals where the enforcement of appropriate prescribing practices is much better [53]. No change was observed in primary care facilities due to the knowledge gap in primary care providers, loose regulation enforcement and a high demand from patients [17,18,54]. Our previous trial in rural Guangxi proved the effectiveness and longterm benefits of educational interventions and prescribing peer-reviews in this setting [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the implementation of the National Essential Medicines Policy and Zero-Mark-Up Policy in 2009 and the Administrative Regulation for Clinical Antibiotic Use in 2012 [16], their effects on reducing inappropriate antibiotic prescribing have been limited to large hospitals where the enforcement of appropriate prescribing practices is much better [53]. No change was observed in primary care facilities due to the knowledge gap in primary care providers, loose regulation enforcement and a high demand from patients [17,18,54]. Our previous trial in rural Guangxi proved the effectiveness and longterm benefits of educational interventions and prescribing peer-reviews in this setting [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, no operational details have been given. The policy has not been proven effective at improving appropriate antibiotic prescribing [17]. Additionally, the policy only focussed on large hospitals and neglected primary care facilities [18,19].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, intervention studies to reduce antibiotic prescribing in primary care are rare in low resource settings . In a natural experimental study, we found that including peer‐review within a stewardship programme may reduce antibiotic prescribing . Thus, we developed an intervention package that aimed to reduce prescribing of antibiotics for URTIs in 2–14‐year‐old outpatients, attending primary care facilities in rural Guangxi, China.…”
Section: Introductionmentioning
confidence: 99%